The Influence of Work-Life Balance, Workload and Burnout on Employee Performance in PT. Siraj Badawi Cukup Rupiah - Panji Agustian; Hilmi Miftah Fadli; Muhamad Farhan Faturahman; Sunimah Sunimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the influence of work-life balance, workload, and burnout on employee performance. The research employs a descriptive quantitative method, utilizing multiple regression analysis with SPSS 26 for data processing. The sample was selected using simple random sampling, where employees from PT. Siraj Badawi Cukup Rupiah was randomly chosen to participate in the survey. A total of 369 questionnaires were distributed, with 110 respondents returning them, yielding a response rate of 29.81%. The findings can be summarized as follows: (1) Work-life balance has a positive but not significant effect on employee performance; (2) Workload has a positive and significant effect on employee performance; (3) Burnout has a significant negative effect on employee performance; (4) Work-life balance, workload, and burnout collectively have a significant impact on employee performance.